Unveiling Seventh-grade Natural Sciences Teaching Practices Under the Merdeka Curriculum in Pontianak, West Kalimantan - Kurnia Ningsih; Anisyah Yuniarti; Mas Akhbar Faturrahman; Dian Wahyuningsih (Universitas Pendidikan Mandalika, 2026)
The Merdeka Curriculum is a systemic change aimed at addressing learning loss caused by the Coronavirus Disease 2019 pandemic. One subject largely affected by the curriculum implementation is Natural Sciences, which has undergone several changes since its inception in 2022. This research aims to examine how the implementation of the Merdeka Curriculum in the seventh-grade Natural Sciences subject has developed over time by comparing its initial adoption with its implementation in 2025. This research employed mixed methods and involved 30 seventh-grade Natural Sciences teachers from junior high schools in Pontianak City, West Kalimantan Province, Indonesia. Data collection involved questionnaires and brief interviews in 2023 and 2025, concluding in quantitative and qualitative data analysis. The research unveiled comprehensive information, mapped into five key aspects of implementing Natural Sciences learning in the Merdeka Curriculum: the subject’s basis and duration, teachers’ perceptions and understanding, planning and implementation of the learning, assessment of the learning, and its impacts. Several notable key quantitative findings were revealed. First, the proportion of schools that implemented the Merdeka Curriculum rose from 93.3% in 2023 to 100.0% in 2025. Second, teachers who utilized four learning models in 2023 began diversifying their choices, with the 2025 data showing five models, with problem-based learning gaining the highest proportion (76.7%). Third, the collaboration among Natural Sciences teachers and other subjects has risen in proportion from 46.7% for both in 2023 to 86.7% and 76.7% in 2025, respectively. Fourth, the proportion of teachers who felt positive impacts from the Merdeka Curriculum rose from 93.3% in 2023 to 100.0% in 2025. Fifth, there is a decrease in the proportion of teachers who faced obstacles in implementing the Merdeka Curriculum—from 90.0% in 2023 to 66.7% in 2025. Moreover, qualitative findings enrich the quantitative data by providing insights into how seventh-grade Natural Sciences teachers perceive the Merdeka Curriculum and how they translate the regulations into classroom practices, thereby supporting students’ further development in line with national and global demands. Overall, the results indicate that the seventh-grade Natural Sciences teachers in Pontianak City perceive the Merdeka Curriculum as a primary nationwide educational framework that substantially improves teachers’ competencies and supports student development, particularly in character development and 21st-century skills. However, several issues in curriculum implementation require further action and research.